Analysis of Man in Saiva Siddhanta & Christianity - Patrick, Rev.Fr.D.V. (Faculty of Graduate Studies, 2012)
This thesis is a holistic attempt to explore the riches of human being in phenomenological and transcendental realm relating to Saiva Siddhanta and Christianity in the context of world religions. The accent here is human being resuming his/her original form. This transition is viable, totalistic, and optimistic, admitting the complexities of human being in relation to others and God. Man or woman is a dynamic being trying to search for meaning in life in a concrete way while making his/her life pleasant. Anything that is human involves change and the human liberation is summed up in the process of humanization which is holistic. In union with God, man or woman moulds his/her own being. Having a sound inter-personal relationship with others, he/she is true to himself/herself, when he/she truly tends to God and reflect Him in his / her entire humanness, body, soul, and sprit. This special relationship between God and human being is explicit both in Saiva Siddhanta and Christianity, focusing self in the universe. Accordingly, concept of human being is closely associated with the divine. The essential feature of this study is based on the following questions: What is human being? Who is this mysterious being that constantly transcends himself/herself in all that he/she thinks, desires, and cts but without fully reaching the goal of truth, goodness, and happiness longed for? How will it be possible to interpret the profound division in human being, in thought and truth, the willing will and the willed will? My main objective in this research is to seek a suitable answer to the above questions. Human being possess the spiritualistic and materialistic components in him/her and he/she become the noble being among all creatures of God in the universe. Faculty to think, reason out, feel, act, and to relate well characterize the nature of human being.